Neodymium doped bismuth telluride alloys using chemical reflux method for thermoelectric application. Issue 184 (13th October 2017) - Puri, Nidhi; Gupta, Raj K.; Mehra, N. C.; Tandon, R. P.; Mahapatro, Ajit K.
ABSTRACT: This work reports synthesis of pure and neodymium (Nd) doped bismuth telluride (Bi2 Te3 ) alloys (Bi2-x Ndx Te3, x = 0, 0.5), using reflux method. The X-ray powder diffraction for the as-synthesized Bi2 Te3 indicates phase purity and crystallographic structure, and agrees well with the prescribed JCPDS data # 000–60601. The Bi2-x Ndx Te3 alloys were characterized by pursuing various imaging and spectroscopic techniques including, scanning electron microscope, and UV-Vis absorption spectroscopy. After Nd doping, the micrographs show formation of a new contrast (white phase) with the prominent (201) plane of a hexagonal crystal structure.